Rosuvastatin: A Potential Therapeutic Agent for Inhibition of Mechanical Pressure-Induced Intervertebral Disc Degeneration - Zhang C; Wang Q; Li K; Fu M; Gao K; Lv C (Dove Medical Press, 2024)
Cunxin Zhang,1,* Qian Wang,1,* Kang Li,1 Maoqing Fu,1 Kai Gao,2 Chaoliang Lv1 1Department of Spine Surgery, Jining No. 1 People's Hospital, Jining, 272011, People's Republic of China; 2Department of Orthopaedics, Jining No. 1 People's Hospital, Jining, 272011, People's Republic of China*These authors contributed equally to this workCorrespondence: Chaoliang Lv, Department of Spine Surgery, Jining No. 1 People's Hospital, No. 6 Healthy Road, Rencheng District, Jining, 272011, People's Republic of China, Tel +86 15265775628, Fax +86-0537- 2253252, Email lvchaolianggk@163.com Kai Gao, Department of Orthopaedics, Jining No. 1 People's Hospital, Jining, No. 6 Healthy Road, Rencheng District, Jining, 272011, People's Republic of China, Tel +86 15853760330, Fax +86-0537- 2253252, Email gaohaikai88@126.comBackground: Intervertebral disc degeneration (IDD) underlies the pathogenesis of degenerative diseases of the spine; however, its exact molecular mechanism is unclear.Purpose: To explore the molecular mechanism of mechanical pressure (MP)-induced IDD and to assess the role and mechanism of Rosuvastatin (RSV) inhibits MP-induced IDD.Methods: SD rat nucleus pulposus cells (NPCs) were cultured in vitro and an apoptosis model of NPCs was constructed using MP. Proliferative activity, reactive oxygen species content, apoptosis, and wound healing were detected in each group of NPCs, respectively. The expression of relevant proteins was detected by qPCR and Western Blot techniques. 18 SD rats were randomly divided into control, pressure and RSV groups. Elisa, qPCR, Western Blot and immunohistochemical staining techniques were used to detect changes in the content of related proteins in the intervertebral discs of each group. HE staining and Modified Saffron-O and Fast Green Stain Kit were used to assess IDD in each group.Results: MP treatment at 1.0 MPa could significantly induce apoptosis of NPCs after 24 h. MP could significantly inhibit the proliferative activity and wound healing ability of NPCs, and increase the intracellular reactive oxygen species content and apoptosis rate; pretreatment with RSV could significantly activate the Nrf2/HO-1 signaling pathway and reverse the cellular damage caused by MP; when inhibit the Nrf2/HO-1 signaling pathway activation, the protective effect of RSV was reversed. In vivo MP could significantly increase the content of inflammatory factors within the IVD and promote the degradation of extracellular matrix, leading to IDD. When the intervention of RSV was employed, it could significantly activate the Nrf2/HO-1 signaling pathway and improve the above results.Conclusion: RSV may inhibit MP-induced NPCs damage and IDD by activating the Nrf2/HO-1 signaling pathway.Keywords: rosuvastatin, intervertebral disc, nucleus pulposus cells, oxidative stress, nuclear factor E2-related factor 2, heme oxygenase-1, quinone oxidoreductase 1